Classification of streets in the city of Dubai (Journal of the College of Basic Education, 2022)
The network of city streets and its highways is the structural element in the urban foundation, and it occupies a large space of it and plays a functional role within it, which results in the final images of its appearance and external form, and through the performance of its function it takes multiple forms that are a reflection of the city’s topographical situation, its material potential and its historical development that has a relationship The area of ​​the land it occupies and its ownership, and regulates the architectural style of the city and facilitates its regional function because the streets, while performing their service, perform two basic functions ( )